Vincent Šikula: a story and fairy-tale narrator - Vitézová Eva (Journal of Language and Cultural Education, 2017)
Vincent Šikula entered (also) children’s literature in the 1960s, i.e. during the years when crucial works of Slovak children’s literature were published. His works are interesting for children even nowadays because they are built on story-telling, interesting language, and, very often, quick action. Šikula’s poetics is based on not underestimating children. He did not determine in advance for whom his books are intended, since, in his opinion, they were appropriated by those whom they suited most. The paper discusses Šikula’s stories and fairy-tales with regard to the authorial narrative strategies.